2013
DOI: 10.1590/1414-431x20132964
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles: structure, function, and potential clinical uses in renal diseases

Abstract: Interest in the role of extracellular vesicles in various diseases including cancer has been increasing. Extracellular vesicles include microvesicles, exosomes, apoptotic bodies, and argosomes, and are classified by size, content, synthesis, and function. Currently, the best characterized are exosomes and microvesicles. Exosomes are small vesicles (40-100 nm) involved in intercellular communication regardless of the distance between them. They are found in various biological fluids such as plasma, serum, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
208
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(232 citation statements)
references
References 55 publications
(70 reference statements)
2
208
0
5
Order By: Relevance
“…Furthermore, as unique markers for the different vesicle types have not yet been fully defined, the origin of vesicles released from cells cannot be identified. For this reason, here we use the collective term EVs [10][11][12][13][14].…”
Section: Extracellular Vesicles/exosomesmentioning
confidence: 99%
“…Furthermore, as unique markers for the different vesicle types have not yet been fully defined, the origin of vesicles released from cells cannot be identified. For this reason, here we use the collective term EVs [10][11][12][13][14].…”
Section: Extracellular Vesicles/exosomesmentioning
confidence: 99%
“…36 Recent studies indicate that exosomes and microvesicles derived from multipotent MSCs have therapeutic promise in cardiovascular, liver, and kidney diseases. 7,17,60 We have previously demonstrated that exosomes generated from MSCs promote neurite remodeling and functional recovery in rats after stroke. 91 As a proof-of-principle study of MSC-exosomes as a novel cell-free alternative therapeutic approach for TBI, we will test the hypothesis that exosomes generated from MSCs when systemically administered to an animal with TBI improve functional outcome, with therapeutic benefits reflecting those observed with systemically administered MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to transplanted exogenous MSCs, nanosized exosomes derived from MSCs do not proliferate, are less immunogenic and easier to store and deliver than MSCs (Lai et al, 2011). Recent studies indicate that exosomes and microvesicles derived from multipotent MSCs have therapeutic promise in cardiovascular, kidney, liver and lung diseases (Akyurekli et al, 2015; Borges et al, 2013; Cosme et al, 2013; Lai et al, 2011; Lai et al, 2015; Liang et al, 2014; Masyuk et al, 2013; Yu et al, 2014). We have demonstrated that exosomes generated from rat MSCs improve functional recovery in rats after stroke (Xin et al, 2013b) and TBI (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%